Empowering Waste Management Community Through Financial Literacy - Ryan Dwitanto, Ardo; Soetiono Sanjaya, Carrisa; Febrianus, Alessandro; Surya Gustin, Alvin (Journal of Sustainable Community Development (JSCD), 2025)
As financial inclusion rates in Indonesia rise without a corresponding increase in financial literacy, financial knowledge has become crucial for Indonesian citizens. Despite this, many individuals, particularly those in rural areas or with limited education, still lack basic financial knowledge. This community involvement initiative aims to address this issue by providing financial literacy education to the waste management community in South Rawabadak, North Jakarta. The program's activities include: 1) Program socialization within the community, 2) Focus group discussions with housewives to gather initial information, and 3) Knowledge sharing sessions on basic financial statements tailored to the gathered information. By providing accessible and relevant financial education, the program empowers the waste management community to make informed financial decisions, manage their resources effectively, and build a more secure financial future. This initiative serves as a valuable model for replicating similar programs across various communities in Indonesia, ultimately contributing to a more financially literate and empowered nation.